Biomechanical guideline values to support gymnasts learning of handspring and double salto forward tucked on vault - Naundorf, F.; Lehmann, T.; Wohlfahrt, L.; Friedl, F. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The vault handspring and double salto forward tucked was already studied biomechanically several times performed 20 or more years ago. However, this vault is still important today. Our aim is to check the validity of the published results under current apparatus conditions using 24 vaults from 24 gymnasts selected via the minimum execution-score (= 9.0) from high level competitions. For this purpose, 14 parameters are evaluated using a 2-dimensional analysis. Compared to published data the results show an increase of the velocity during the flight to the vaulting board. There is no notable change in the maximum height of the body center of mass in the post flight. Our new results are the basis for a comparison of one example national gymnast in an infographic, in which strengths and weaknesses are recognizable and should support the coach in his work.